Student Perceptions of Learning Vocabulary Through Task-Based Learning (TBL): A Case Study - Amelia Amelia; Iwan Ridwan; Abdul Kodir Al-Baekani (FKIP - Universitas Riau, 2026)
Vocabulary is a fundamental component of English language learning as it supports the development of other language skills. However, many students still experience difficulties in vocabulary acquisition due to monotonous teaching methods and limited use of interactive learning media. This study aims to investigate senior high school students’ perceptions of learning vocabulary through Task-Based Learning (TBL) integrated with crossword puzzles. A qualitative approach with a case study design was employed, involving eleventh-grade students from a senior high school in Karawang. Data were collected through classroom observations and semi-structured interviews and analyzed using thematic analysis. The findings revealed that the integration of crossword puzzles within the TBL framework created a more engaging, interactive, and meaningful learning environment. Students showed increased motivation, active participation, and better understanding of vocabulary across the pre-task, during-task, and post-task stages. They perceived vocabulary learning as enjoyable, less stressful, and effective in helping them remember and apply new words in context. In conclusion, the use of Task-Based Learning combined with crossword puzzle media positively influenced students’ vocabulary learning experiences, motivation, and confidence.